Preferences and Willingness to Pay for Preservation: The Case of a Proposed Hydropower Project in Southern Iceland - Clint Cook; Anna Dóra Sæþórsdóttir; David Cook (Land, 2024)
When decision makers use a financial approach to review the costs and benefits of new renewable energy projects, the economic value of changes in social welfare resulting from impacts on natural resources is not included in the analysis. Iceland’s policy objective for carbon neutrality by 2040 will require constructing new power plants. This study aimed to estimate the economic preservation value for the Hólmsá and Tungufljót river basins in southern Iceland using the contingent valuation method. A web-based survey of Icelandic residents was conducted between 13 November 2022 and 19 December 2022 using a stratified random sample of 2909 adults. The response rate was 46.6%, with 35.1% of respondents indicating a willingness to pay (WTP) to protect the area from hydropower development. After excluding protest voters and accounting for those with and without WTP, the estimated mean WTP equaled ISK 5515. When scaled to the adult population of Icelandic residents, that equates to a total environmental and social cost of between ISK 1.52 and 1.70 billion. Compared to the estimated levelized cost of energy for the Hólmsárvirkjun at Atley hydropower project, this aggregation equates to an estimated 5.6% markup in total project costs, excluding transmission lines. Accounting for these economic costs in decision making allows for a more holistic understanding of new energy project costs and net present benefits.